UTILITY OF ALCOHOL SALIVA STRIP TEST FOR DETECTION OF ALCOHOL IN ROAD TRAFFIC ACCIDENT CASES: AN AUTOPSY STUDY (Journal of Forensic Medicine & Toxicology, 2023)
Alcohol consumption is the major factor in road traffic accidents. Road traffic accident related autopsies are one of the major components in the total autopsies in any institution. It’s not possible to preserve the viscera of each and every autopsy case as it can cause excess burden on our forensic laboratory financially as well as physically. The alcohol saliva strips is a new rapid tool for the estimation of blood alcohol concentration. The current study is undertaken to find out the sensitivity and significance of alcohol saliva strip method to detect the presence of alcohol in samples of saliva/oral secretion in an autopsy scenario. Alcohol saliva strips were found useful for the detection of the alcohol in cases where color change on the reactionary pad of the alcohol saliva strips is visible and comparable with the standard color mentioned on the packet. However, it was not much of use for the measurement of blood alcohol concentration.
Keywords: Alcohol; Alcohol saliva strip test; Blood alcohol concentration; Drunkenness; Toxicology